Enhancing economics education through phenomenography, variation theory, and multiple representations - Bamiro, Nurudeen Babatunde; Zakariya, Zainizam; Yahya, Lateefat Oludare; Mohammed, Abidat Oluwashola (Faculty of Engineering, Universitas Negeri Yogyakarta, 2024)
This study explores the intersection between phenomenography and variation theory in educational settings, focusing on their implications for teaching economics. Phenomenography, a research approach aimed at understanding how individuals perceive and conceptualize phenomena, provides insights into learners' diverse interpretations of concepts. Variation theory, derived from phenomenography, guides instructional design by emphasizing the importance of experiencing variations in critical aspects of the learning material. The study investigates whether employing multiple representations enhances knowledge transfer, learning outcomes, and concept variation. The findings suggest that integrating variation theory into economics classrooms can optimize students' understanding by directing attention to critical aspects of concepts through varied instructional strategies.